Man up [videorecording (DVD)] - Pegg, Simon, 1970-; Bell, Lake, 1979-; Kinnear, Rory, 1978-; Stott, Ken, 1955- (Lionsgate, 2016)
When Nancy is mistaken for Jack's blind date, she decides to take fate into her own hands and just go with it. What could possibly go wrong?